2002
DOI: 10.1001/jama.288.16.2008
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation in Obese Women

Abstract: Android obesity is associated with enhanced lipid peroxidation and persistent platelet activation. These abnormalities are driven by inflammatory triggers related to the degree of abdominal adiposity and are, at least in part, reversible with a successful weight-loss program.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
95
2
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 499 publications
(106 citation statements)
references
References 46 publications
6
95
2
3
Order By: Relevance
“…This difference is consistent with other reports of a sex difference in brain reserve and clinical manifestations of AD pathologic changes, 19–21 although this association remains a point of discussion. Importantly our results also showed that both smoking and increased BMI, already know to be associated with increased free radical injury in peripheral organs, 22,23 were also associated with increased CSF F 2 -isoprostanes. Thus avoidance of smoking and reducing BMI, in addition to their already established benefits, may also be beneficial in reducing molecular and cellular stress to our brains.…”
Section: Discussionsupporting
confidence: 78%
“…This difference is consistent with other reports of a sex difference in brain reserve and clinical manifestations of AD pathologic changes, 19–21 although this association remains a point of discussion. Importantly our results also showed that both smoking and increased BMI, already know to be associated with increased free radical injury in peripheral organs, 22,23 were also associated with increased CSF F 2 -isoprostanes. Thus avoidance of smoking and reducing BMI, in addition to their already established benefits, may also be beneficial in reducing molecular and cellular stress to our brains.…”
Section: Discussionsupporting
confidence: 78%
“…MetS and diabetes mellitus are well known causes of CVD. In addition, obesity by itself is related to atherosclerosis, hypertension and prothrombotic complications (22,23). Many studies have shown that LDL is increased in women with PCOS (24).…”
Section: Discussionmentioning
confidence: 99%
“…Both obesity and diabetes have been shown to be associated with oxidative stress [75][76][77][78] and inflammation [79][80][81][82][83]. The concentration of pro-inflammatory cytokines including TNF is elevated in T2D [81] and may contribute to HH in this condition.…”
Section: E) Role Of Inflammationmentioning
confidence: 99%